Canadian market access requirements for black maca cookies - Cespedes Rosales, Fabiola Milagros (2020)
Develop an insertion plan for black maca cookies to the canadian market. The investigation done was not experimental. To develop this paperwork we rely on past investigations made. The development of an export plan allows the easy insertion of cookies made of back maca. Canada is a convenience market because the consumers have preference for organic products. The international fairs are fundamental tools because it allows the meet between the exporter and importer.